2015
DOI: 10.12657/folmal.023.003
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic status of Stagnicola palustris
 (O. F. Müller, 1774) and S. turricula (Held, 1836) (Gastropoda: Pulmonata: Lymnaeidae) in view of new molecular and chorological data

Abstract: Analyses of nucleotide sequences of 5'-and 3'-ends of mitochondrial cytochrome oxidase subunit I (5'COI, 3'COI) and fragments of internal transcribed spacer 2 (ITS2) of nuclear rDNA gene confirmed the status of Stagnicola corvus (Gmelin), Lymnaea stagnalis L. and Ladislavella terebra (Westerlund) as separate species. The same results showed that Stagnicola palustris (O. F. Müll.) and S. turricula (Held) could also be treated as separate species, but compared to the aforementioned lymnaeids, the differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The distinction between M. cartusiana and M. claustralis is not as clear-cut as presented by Pieńkowska et al (2015Pieńkowska et al ( , 2018. Specimens with M. claustralis haplotype but with a bulge on vagina from the Prokopské Valley in Prague, Choteč and Nučice led us to examine the population in Nučice more closely in 2015.…”
Section: Menetus Dilatatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinction between M. cartusiana and M. claustralis is not as clear-cut as presented by Pieńkowska et al (2015Pieńkowska et al ( , 2018. Specimens with M. claustralis haplotype but with a bulge on vagina from the Prokopské Valley in Prague, Choteč and Nučice led us to examine the population in Nučice more closely in 2015.…”
Section: Menetus Dilatatusmentioning
confidence: 99%
“…Monacha claustralis (Rossmässler, 1834)Pieńkowska et al (2015) found that there are two species of Monacha in the Czech Republic. Besides M. cartusiana (O. F., which is spreading in the Czech Republic since 1990s(Kolouch 1996, 2005, Ložek 1999, Peltanová et al 2012), they reported its close relative M. claustralis Rossmässler, 1834, found among Monacha samples from Prague.…”
mentioning
confidence: 99%
“…A review of the European Lymnaeidae based on a molecular survey showed that S. turricula may not be considered to be a species that is independent from S. palustris [45]. However, the result of Pie ńkowska et al [46] confirmed the separate status of S. turricula as a species. According to Hill et al [21], perennial floodplain meadow ponds support more gastropod species than ephemeral ponds including lymnaeid species such S. palustris and R. balthica.…”
Section: Natural Aquatic Habitats Along the River Valley As Refuges F...mentioning
confidence: 99%
“…The percentage of identity varied from 90.18 to 98.93% in this dataset. In addition, COI sequences of other species of Ampullaceana, A. lagotis, A. balthica, A. ampla and others, were included in the analysis (Aguilar, Ogburn & Hines, unpublished;Aksenova et el., 2016;Aksenova et al, 2017;Aksenova et al, 2018;Albrecht et al, 2004;Albrecht et al, 2008;Albrecht et al, 2014;Dewaard, unpublished;Grabner et al, 2014;Hebert et al, unpublished;Klussmann-Kolb et al, 2008;Leerhoei, unpublished;Mirfendereski et al, 2021;Nasibi et el., unpublished;Paltser et al, unpublished;Pantoja et al, 2021;Patel et al, 2015;Pfenninger et el., 2003;Pfenninger, Cordellier & Streit, 2006;Pienkowska et al, 2015;Schniebs et al, 2018;Schniebs et el., unpublished;Vinarski et al, unpublished a;Vinarski et al, unpublished b;Wethington & Guralnick, unpublished;Young et al, 2021) (see Table 1). More distant species of the family Lymnaeidae Rafinesque, 1815 were analysed as outgroups that included Lymnaea stagnalis (L., 1758) (13 sequences), Radix auricularia (L., 1758) (14 sequences) and Stagnicola palustris (Müller, 1774) (12 sequences).…”
Section: Phylogenetic Analysismentioning
confidence: 99%